2006
DOI: 10.1158/0008-5472.can-06-2387
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Tissue Transglutaminase in Pancreatic Ductal Adenocarcinoma and Its Implications in Drug Resistance and Metastasis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive neoplastic diseases and is virtually incurable. The molecular mechanisms that contribute to the intrinsic resistance of PDAC to various anticancer therapies are not well understood. Recently, we have observed that several drugresistant and metastatic tumors and tumor cell lines expressed elevated levels of tissue transglutaminase (TG2). Because PDAC exhibits inherent resistance to various drugs, we determined the constitutive expression of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
147
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 36 publications
15
147
0
Order By: Relevance
“…It has been shown that TGM2 promotes cell growth, survival, and motility or invasion (38,39). Although increased TGM2 expression in cancer cells has been linked to increased drug resistance, metastasis, and poor patient survival (36,37,40), to our knowledge, this is the first report showing that TGM2 is overexpressed when acquired TRAIL resistance arises with the association of increased cell migration and invasion.…”
Section: Discussionmentioning
confidence: 79%
“…It has been shown that TGM2 promotes cell growth, survival, and motility or invasion (38,39). Although increased TGM2 expression in cancer cells has been linked to increased drug resistance, metastasis, and poor patient survival (36,37,40), to our knowledge, this is the first report showing that TGM2 is overexpressed when acquired TRAIL resistance arises with the association of increased cell migration and invasion.…”
Section: Discussionmentioning
confidence: 79%
“…Increased TG2 tissue levels have been observed in neurodegenerative diseases (28), including Alzheimer's, Huntington's, and Parkinson's diseases, as well as in chronic inflammatory conditions such as celiac disease (29). Increased tissue levels of TG2 have also been detected in cancer such as glioblastomas, malignant melanomas, and pancreatic ductal adenocarcinomas (30), and they are often associated with an increased metastatic activity or acquisition of drug resistance (30).…”
Section: Ystic Fibrosis (Cf)mentioning
confidence: 99%
“…Efforts to identify proteins in these breast-cancer cells, whose expression was up-regulated by EGF and therefore, potentially could contribute to its growth-promoting activity, led us to tTG, a dual-function enzyme that couples an ability to bind and hydrolyze GTP with a transamidation activity that cross-links proteins through glutamine-lysine or glutamine-polyamine linkages. Whereas there have been suggestions that chronic tTG expression and/or activation associated with some human cancers is linked to their malignant transformation (10)(11)(12)(13)(14)(15)(16), an understanding of how tTG is regulated in cancer cells and whether or not there is a functional relationship between this protein and EGFpromoted tumor growth has been lacking. Fig.…”
Section: Resultsmentioning
confidence: 99%